Effect of Curing Temperature on the Durability of Concrete under Highly Geothermal Environment - Yang Tang; Hui Su; Shun Huang; Chunlai Qu; Jiaqi Yang (Advances in Materials Science and Engineering)
To determine the durability of concrete in the actual temperature and humidity of the tunnel environment, this study investigates the mechanical properties, permeability of chloride ion, relative dynamic elastic modulus, and mass loss ratio of concrete specimens cured in the temperature which varied from normal, 40, 60, 75, and 90°C, and the humidity was kept at 90% continuously. Experimental results reveal that the hot temperature curing environment may benefit early stage strength development but reduce the long-term strength. It is proved that 60°C is a critical point. At above 60°C, the strength of the concrete material and its resistance to chloride ion permeability showed a decreasing trend; however, in the appropriate temperature range, the frost resistance properties of the concrete are improved with increasing temperature.